Hox genes: realising the importance of realisators - Lohmann, Ingrid (Current biology, 2006)
A recent study for the first time unravels a complete Hox regulatory network sufficient for the specification of a simple organ in Drosophila, linking Hox output to one specific group of executive genes, the realisators. As these genes have a direct effect on cellular functions and are required in most cell types, Hox genes may ultimately execute their function in controlling segmental fate by fine-tuning the spatial and temporal expression levels of these realisators.